THE EFFECTIVENESS OF LERCANIDIPINE IN REDUCING THE RISK OF ARTERIAL HYPERTENSION COMPLICATIONS - E. EL. Trisvetova (Столичная издательская компания, 2015)
Despite progress in reducing the risk of hypertension (HT) complications, control of blood pressure (BP) levels remains inadequate. Dihydropyridine calcium channel blockers show antihypertensive effect due to significant vasoselective action with a minimal impact on a conductive system of the heart. Lercanidipine is a dihydropyridine calcium channel blocker of the third generation with high lipophilicity and long-lasting action. Lercanidipine had shown both in monotherapy and in combination with ACE inhibitors or angiotensin II blockers the good antihypertensive effect with stable BP profile throughout the day, organoprotection that slowed down the progression of HT complications, metabolic neutrality and safety in mild to moderate HT.